Disclosure of physical, emotional and sexual child abuse, help-seeking and access to abuse response services in two South African Provinces. (6th March 2017) - Meinck, Franziska; Cluver, Lucie; Loening-Voysey, Heidi; Bray, Rachel; Doubt, Jenny; Casale, Marisa; Sherr, Lorraine
Abstract: Physical, emotional and sexual child abuse are major problems in South Africa. This study investigates whether children know about post-abuse services, if they disclose and seek services, and what the outcomes of help-seeking behaviour are. It examines factors associated with request and receipt of services. Confidential self-report questionnaires were completed by adolescents aged 10–17 ( n = 3515) in South Africa. Prevalence of frequent (>weekly) physical abuse was 7.4%, frequent emotional abuse 12.4%, and lifetime contact sexual abuse 9.0%. 98.6% could name one suitable confidante or formal service for abuse disclosure, but only 20.0% of abuse victims disclosed. Of those, 72% received help. Most common confidantes were caregivers and teachers. Of all abuse victims, 85.6% did not receive help due to non-disclosure or inactivity of services, and 14.4% received help: 4.9% from formal health or social services and 7.1% through community vigilante action. Emotional abuse, sexual abuse and female gender were associated with higher odds of help-seeking. While children in South Africa showed high knowledge of available services, access to and receipt of formal services among abused children was low. Notably fewer children received help from formal services than through community vigilante action. Urgent action is needed to improve service access for child abuse victims.